Energy efficient and alternative air distribution system for Dewan Sri Budiman / Mohd Nazre Mardzuki and Sanusi Maulod - Mardzuki, Mohd Nazre; Maulod, Sanusi (1993)
The project undertaken by us is to identify or to analyse the present air conditioning units at the Dewan Sri Budiman as to how the units are performing. Wherever necessary, from our findings, we have to come up with a proposal of up-grading the present units with suggestions as to how the improvement could be done. The aims of the project basically, is to save the energy usage by the existing units or finding ways of reducing the energy conservation by the units if possible. As we know, air conditioning system in the buildings are known to be the largest energy consumer in term of the kilowatts used of electricity. Therefore proper maintenance of the units must be taken care by the owner so as to ensure maximum operating efficiency. The initial stage of selecting the right air conditioning system of the proper design on the load requirements is very crucial so as to ensure evenly distributed cooling throughout the dewan.